2008
DOI: 10.1111/j.1399-5448.2007.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained IL-1α, IL-4, and IL-6 elevations following correction of hyperglycemia in children with type 1 diabetes mellitus

Abstract: Objective:  An imbalance of pro‐/anti‐inflammatory cytokines may accelerate diabetic vascular complications and interfere with proper wound healing. Currently, limited available literature suggests that plasma concentrations of certain pro‐ and anti‐inflammatory cytokines may be altered during hyperglycemia/diabetes mellitus. It is still unclear, however, whether these concepts also apply to children with diabetes, and whether alterations in circulating cytokine levels are a permanent feature of diabetes or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 46 publications
3
43
2
3
Order By: Relevance
“…However, others have found that hyperglycemia does not itself increase the production of IL1β because blood obtained from patients before the overt development of T1D had elevated IL1β expression, whereas patients with long-standing diabetes in suboptimal glycemic control did not (14). In addition, when patients with long-standing T1D were made acutely hyperglycemic, their IL1β levels were not different from those of the control group, but another proinflammatory cytokine, IL1α, was elevated in the patients with marked hyperglycemia (15). Because IL1α binds to the same receptor as IL1β, this finding would suggest that IL1α could contribute to the chronic inflammation associated with T1D.…”
Section: Studies Of Il1β In Human T1dmentioning
confidence: 96%
“…However, others have found that hyperglycemia does not itself increase the production of IL1β because blood obtained from patients before the overt development of T1D had elevated IL1β expression, whereas patients with long-standing diabetes in suboptimal glycemic control did not (14). In addition, when patients with long-standing T1D were made acutely hyperglycemic, their IL1β levels were not different from those of the control group, but another proinflammatory cytokine, IL1α, was elevated in the patients with marked hyperglycemia (15). Because IL1α binds to the same receptor as IL1β, this finding would suggest that IL1α could contribute to the chronic inflammation associated with T1D.…”
Section: Studies Of Il1β In Human T1dmentioning
confidence: 96%
“…Thus, according to a study of 22 children with T1DM, Rosa and cols. (23) reported that acute hyperglycemia was associated with increased levels of IL6, IL4, and IL1, and these elevated levels persisted for at least 2 h after glucose control. On the other hand, a number of studies have found no such associations (16,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared with individuals with T2DM or obese and normal-weight control subjects, youth with T1DM had lower intrahepatic, visceral, and intramyocelluar fat, BP, and triglycerides and higher HDL and adiponectin than expected. 84,244,245 Also unexpectedly, intra-abdominal fat volume did not correlate with IR in adult women with T1DM. 248 Thus, the mechanisms of IR likely differ between T1DM and T2DM, requiring further research to customize treatment strategies.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 98%
“…84 Importantly, IR (low GDR) is associated with a more atherogenic fasting lipid profile and lipoprotein subfraction cholesterol distribution and decreased cardiopulmonary fitness and vascular reactivity. 84,[243][244][245] Although long-term data linking IR in T1DM youth to negative long-term cardiovascular outcomes in T1DM adults are lacking, IR correlates with coronary artery calcification, 246 coronary artery disease, and actual cardiovascular events. 154,247 These data argue that IR in T1DM has effects on the cardiovascular system similar to those seen in T2DM.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation